Dynamical and chemical evolution of the thin disc - Just, Andreas; Rybizki, Jan (Astronomische Nachrichten, 2016)
Our detailed analytic local disc model (JJ-model) quantifies the interrelation between kinematic properties (e.g. velocity dispersions and asymmetric drift), spatial parameters (scale-lengths and vertical density profiles), and properties of stellar sub-populations (age and abundance distributions). Any consistent radial extension of the disc evolution model should predict specific features in the different distribution functions and in their correlations. Large spectroscopic surveys (SEGUE, RAVE, APOGEE, Gaia-ESO) allow significant constraints on the long-term evolution of the thin disc. We discuss the qualitative difference of correlations (like the α-enhancement as function of metallicity) and distribution functions (e.g. in [Mg/H] or [Fe/H]) for the construction of a disc model. In the framework of the JJ-model we build a local chemical enrichment model and show that significant vertical gradients for main sequence and red clump stars are expected in the thin disc. A Jeans analysis of the asymmetric drift provides a link to the radial structure of the disc. The derived metallicitydependent radial scale-lengths can be combined in the future with the abundance distributions at different Galactocentric distances to construct full disc models. We expect to be able to constrain possible scenarios of inside-out growth of the thin disc and to characterise those populations, which require significant radial migration.
Gesehen am 06.11.2017